Hubungan Metode Pembelajaran Alquran dengan Minat Belajar Peserta Didik pada Progam Tahsin Tilawah di Masjid Raya Korong Pasir Baru Kecamatan Sungai Limau Kabupaten Padang Pariaman - Ulfi Ulfi; Jalius Jalius (Universitas Negeri Padang, 2022)
This study was motivated by students’ low interest in learning the tahsin reading program at the Korong Pasir Baru Mosque, Sungai Limau District, Padang Pariaman Regency. This is prabably related it has something to do with the use of learning methods used by teachers.This type of research is quantitative using a correlational approach. The population of this research were all students of recitation recitations at the Great Mosque of Korong Pasir Baru was totalled 30 people and taking a sample of 24 people. Data collection methode using a questionnaire. We used the percentage and the correlation Spearman formula as the data analysis. The results showed that the Qur'anic learning method was categorized as low, students' interest in learning was still low, and there was a considerable relationship either the Koranic learning method and students' learning interest in the recitation program at the Korong Pasir Baru Grand Mosque, Sungai Limau District, Padang Pariaman Regency. It is hoped that teachers will pay more attention to the use of learning methods because this affects students' interest in learning. the better the learning method used, the higher the learning interest of students. And vice versa learning methods that are not good will affect the learning interest in student.